Preliminary feasibility for public research & development projects - Yoon, Donghun (Emerald Publishing Limited, 2021)
Research and development infrastructures are a critical success factor in the platform of science and technology. In turn, an R&D preliminary feasibility study is essential to establish fairness and social credibility of a plan, including expert review, information disclosure and alternative setting. Preliminary Feasibility for Public Research & Development Projects explains how to evaluate R&D business by exploring the five key features of policy implication, policy improvement, preliminary feasibility study, R&D evaluation, and R&D strategy. Presenting policy measures to ensure the sustainability of R&D projects, Preliminary Feasibility for Public Research & Development Projects will help develop strategic measures for R&D preliminary feasibility studies while proposing ways to enhance the effectiveness of these studies, promote efficiency in public investment projects, and enhance the financial efficiency of large investment projects.
Includes index.
Keywords: Feasibility studies.; Research and development contracts.; Science and state.; Technology and state.; Social Science -- Research.; Research methods: general.; elektronické knihy; electronic books